Park Area Development Plan in Response to the Government Policies and Standards: Case Study of Krathumbaen Municipality, Samut Sakhon - Khongouan, Waralak; Khamwachirapithak, Putpunnin (Journal of Architectural/Planning Research and Studies (JARS), 2020)
As a result of the current urban development situation concentrating on economic growth, implementing government policies and standards in the development of urban parks has often been neglected. However, one area that is an example of the response to government policies and standards for park area development is Krathumbaen Municipality, Samut Sakhon Province. In addition, this research article has its goals to study the park area’s situation and the citizens’ opinions towards the park area development and to analyze the guidelines for the park area development in Krathumbaen Municipality, Samut Sakhon Province where is efficient and responds to government policies and standards through research tools, such as questionnaire preparation, field survey, and interviews. According to the research’s results, it was found that the success of the park area development in Krathumbaen Municipality is a result of consideration of accessibility and activities. Also, the important factors that cause the changes of land utility in the city are government policies. From the interview with the mayor of Krathumbaen Municipality, he has seen how the quality of life of people in the community is. Therefore, there has been trying to change the land to become a green and garden area and a park area continuously. The guidelines for the development of the park area in response to government policies and standards and in line with the opinions of citizens and government agencies in the area, such as promoting and campaigning for an increase in the elderly’s use of the park, promoting public participation in the park area management, promoting the park area’s service quality criteria and physical development.